Design of Highly Porous Materials Based on Chitosan/Pectin Interpolyelectrolyte Complex for Wound Healing Application - Aliaksandr Kraskouski; Maksim Mashkin; Viktoryia Kulikouskaya; Viktoryia Savich; Anastasiya Sidarenka; Sergei Pinchuk; Ruibin Li (Advances in Polymer Technology)
Interpolyelectrolyte complexes (IPECs) of polysaccharides are multifunctional polymer materials that improve the mechanical and physicochemical properties of individual polysaccharides. In this study, highly porous (>90%) materials based on IPECs of versatile natural polysaccharides, chitosan (30 and 1,200 kDa) and pectin, are obtained by freeze-drying technique. To enhance the interaction between chitosan and pectin macromolecules, the latter are chemically functionalized with dialdehyde groups. The chitosan-/aldehyde-functionalized pectin (Chit/AF-Pect) polyelectrolyte complex sponges obtained are characterized using SEM, FTIR spectroscopy, and TGA. The swelling capacity study reveals a higher swelling ratio of IPEC sponges with an increase in both the molecular weight and content of chitosan: for Chit30/AF-Pect, the swelling ratio rises from 327% to 480%, while for Chit1200/AF-Pect, from 681% to 1,066%. Additionally, the in vitro degradation test demonstrates higher stability of Chit1200/AF-Pect sponges in comparison with those of Chit30/AF-Pect: after 4 days of incubation, the weight losses are found to be 9%–16% and 18%–41%, respectively. The cytotoxicity study shows that Chit30/AF-Pect sponges are noncytotoxic, with cell viability values >70%. Furthermore, the Chit30/AF-Pect sponges, obtained at chitosan:pectin weight ratio of 5:1, exhibit bactericidal activity against Escherichia coli BIM B-984 G, Pseudomonas aeruginosa BIM B-807 G, Staphylococcus aureus BIM B-1841, and slightly inhibit the growth of Enterococcus faecalis BIM B-1530 G. These findings indicate that the obtained Chit30/AF-Pect sponges can be used to create wound dressings for wound healing applications.